SOCIAL CHANGE ACCORDING TO BULGARIAN NEW AGE (Религиски дијалог и соработка, 2023)
The modern world citizen today rejects Christian morality as retrograde. Thus,a modern, syncretic, and global alternative to the human self emerges – New Age movement,which is becoming more widespread and sought after by quickly solving life’s problemsand ensuring personal happiness.The cultural Christianity of the Bulgarians facilitates the spread of New Age beliefs andpractices: the historically established “pagan Christianity” of the Bulgarians is manifestedby latent religiosity, dualistic, rich mythological demonology, and oral patriarchal tradition.At first sight, Bulgarian New Age is a liberal religion (according to Peter Beyer): tolerantand ecumenical, with the aim of including more people to work for the benefit of theworld community. But more in-depth research reveals that the proximity in the doctrinesof Bulgarian New Age and Bulgarian Orthodoxy in everyday life allow their conflict-freecoexistence. Additionally, the sociological interpretation of Mark Satin’s quadrant showsthat, unlike the Western New Age, Bulgarian New Age beliefs and practices represent aconservative response to life’s challenges, closer to monolithic institutions than biolithicones: “the path of freedom = the path of suffering = the path of redemption”. Therefore,both the Bulgarian “high” New Age and Bulgarian Orthodoxy are two conservative responsesin a globalized and secularized world. Interpreted through Orthodox theology,Bulgarian New Age is a commune movement: “from below”, organic, informal, non-legal,non-institutionalized, non-hierarchical. In functional terms, it represents a “synthetic metanarrative”of traditional Bulgarian Orthodoxy and particularly Petar Danov’s teaching,which derives its strength from the claim for Bogomil heritage and avoiding the “confessionalcurse”, and the social change needs time and hard self-work.